2011
DOI: 10.1007/s10620-010-1543-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-Jewish Israeli IBD Patients Have Significantly Higher Glutathione S-Transferase GSTT1-Null Frequency

Abstract: GSTT1-null appears to be associated with IBD, while GSTM1-null appears to be conversely associated with IBD. No association was found between GSTT1-null or GSTM1-null and specific IBD phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 34 publications
0
27
1
Order By: Relevance
“…This family presents a strong genetic variability among human populations and its molecular diversity is determined by ethnic background [21]. The null polymorphic variants (homozygous for nonfunctional allele) GSTM1 and GSTT1 have been associated with a variety of health problems, such as high blood pressure in subjects from India and with the development of inflammatory bowel disease in non-Jewish patients from Israel [22, 23]. The allelic frequency of those genes showed considerable variation among Native Americans from Venezuela, where 15.2% of the Panare and 54.3% of Bari tribes presented GSTM1 null genotype whereas none of the Pemon/Warao and 11.4% of Bari tribes presented GSTT1 null genotype [24].…”
Section: Gst and Mercury Exposurementioning
confidence: 99%
“…This family presents a strong genetic variability among human populations and its molecular diversity is determined by ethnic background [21]. The null polymorphic variants (homozygous for nonfunctional allele) GSTM1 and GSTT1 have been associated with a variety of health problems, such as high blood pressure in subjects from India and with the development of inflammatory bowel disease in non-Jewish patients from Israel [22, 23]. The allelic frequency of those genes showed considerable variation among Native Americans from Venezuela, where 15.2% of the Panare and 54.3% of Bari tribes presented GSTM1 null genotype whereas none of the Pemon/Warao and 11.4% of Bari tribes presented GSTT1 null genotype [24].…”
Section: Gst and Mercury Exposurementioning
confidence: 99%
“…Duncan et al showed the GSTT1 null genotype increased UC susceptibility but was not associated with CD [17]. Conversely, Karban et al reported the GSTT1 null genotype increased susceptibility to CD but not UC [20]. Ernst et al reported the GSTT1 null genotype was not associated with UC or CD [19].…”
Section: Introductionmentioning
confidence: 99%
“…[917] As recently reviewed, the prevalence of GSTM1 null allele ranges from 22% in Africans to 62% among Europeans, whereas GSTT1 null status differs from 20% to 60% in Caucasian and Asian people, respectively. [2122] Due to the important role of GSTs in oxidative stress and detoxifying carcinogens, GSTM1 and GSTT1 allelic polymorphisms may result in less effective removal of intestinal toxic metabolites, thus modifying the susceptibility to UC and CD. [2142223]…”
Section: Introductionmentioning
confidence: 99%
“…[2122] Due to the important role of GSTs in oxidative stress and detoxifying carcinogens, GSTM1 and GSTT1 allelic polymorphisms may result in less effective removal of intestinal toxic metabolites, thus modifying the susceptibility to UC and CD. [2142223]…”
Section: Introductionmentioning
confidence: 99%